Impact of Collaborative Learning on Student Teachers’ Comprehension and Attitudes Towards Environmental Education Concepts in Chemistry (International Journal of Scientific Research and Management (IJSRM), 2022)
The study explored the impact of of collaborative learning on student teachers’ comprehension and attitudes towards environmental education concepts in Chemistry. The study involved 64 student teachers studying environmental chemistry at Mufulira College of Education in Zambia. The action research adopted a pre-test post-test quasi-experimental design. The students were randomly assigned to the two intervention groups. In both groups students had opportunities to learn pollution, waste management and climate change. In the experimental group they used team based learning while in the comparison group students used think-pair-share learning. Overall, learners’ attitudes towards chemistry were improved from pre-test to post-test in both the experimental group. Results from the achievement test revealed a statistically significant difference (t (df, 62) = 2.030, p = .024 at α = .05) between the mean scores of the experimental group (Mean = 69.75; SD = 13.853) and the comparison group (Mean = 60.67; SD = 14.501) after the experimental Phase. Overall, both forms of collaborative learning incorporating environmental education concepts and issues in Chemistry had a positive impact on learners’ comprehension and attitudes towards chemistry.